The contribution of the visual narrative in manga to the development of reading competence at the initial level of German language learning - Marija B. Nijemčević Perović; Georgina V. Frei (University of Belgrade, Teacher Education Faculty, 2023)
The aim of the paper is to examine the didactic potential of the visual narrative in manga for developing reading competence at the initial level of German language learning. A semi-structured group discussion was used as a data collection technique in our qualitative research. After the procedure of the semi-structured group discussion, the obtained data were categorized and analyzed. The results show that manga is a part of the authentic culture of the respondents in the period of early adolescence. The dialogue between the textual and images facilitates the construction of meaning and contributes to the development of the reading competence in students at the initial level of foreign language learning. Owing to the faithfulness of the figural representation and the semiotic functions of the specific animation style, manga readers are invited to recognize the emotions and cognitive processes of the characters, which puts the focus on affective factors and aesthetic competences, but also the use of reading strategies (global strategies, problem-solving strategies, and auxiliary strategies). Given that the meaning of the text and its interpretation derive from the image, the interpretation of the iconic elements is considered the first stage in learning to read, and visual narrative is a real need of today's visual generation.